Determinan Firm Value pada Perusahaan Property dan Real Estate Tahun 2017-2021 - Annisa Widya Kurniawati; Yuli Chomsatu Samrotun; Anita Wijayanti (Ekonomis: Journal of Economics and Business, 2023)
Firm value is the investor's perception of the company. Firm value is very important because it reflects the company's performance which can affect investors' perceptions of the company. Companies that have high value will always improve their performance so that it becomes higher and makes potential investors invest as much as possible. Potential investors will be interested in investing in the company and will increase the share price. This study aims to examine and analyze the effect of profitability, leverage, firm size, debt policy and liquidity on firm value. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021 with a total of 81 companies. Sampling using purposive sampling method and samples obtained as many as 15 companies. The sampling criteria are as follows: 1) property and real estate companies are listed on the IDX in 2017-2021; 2) property and real estate companies that publish complete financial reports for 2017-2021; 3) property and real estate companies whose financial reports use the rupiah currency; and 4) property and real estate companies that generate profits in 2017-2021. The data analysis technique uses multiple linear analysis. The results of this study indicate that profitability affects firm value. Leverage affects the value of the company. Firm size has an effect on firm value. Liquidity affects the value of the company. Meanwhile, debt policy has no effect on firm value.